Carbon black particles and preparation method and application thereof
Carbon black particles are prepared by controlling the dehydrogenation polymerization reaction temperature and acetylene gas inlet rate, and improving their pore structure through activation, the problem of insufficient performance of the negative electrode material of sodium ion battery is solved, and the effect of high electrochemical performance and long cycle life is achieved .
Patent Information
- Application Number
- CN202411281241.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The existing sodium ion batteries are difficult to meet the needs of market applications due to their low electrode discharge capacity, short cycle life and poor rate performance. In particular, the performance of negative electrode materials cannot replace lithium ion batteries.
By heating the tube furnace to the dehydrogenation polymerization temperature under the protection of inert gas, perform dehydrogenation polymerization and control the inlet rate of acetylene gas, carbon black particles with suitable particle size and large specific surface area are prepared, and opened by activation of nitric acid The pores of carbon black improve their embeddedness and removal performance as the negative electrode material of sodium ion battery.
The prepared carbon black particles exhibit excellent electrochemical performance as the negative electrode material of sodium ion battery. The first round of charge and discharge specific capacity is high and the discharge specific capacity remains large after cycling, and have good rate performance.
Smart Images

Figure CN119144173A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery carbon materials, and in particular to carbon black particles and a preparation method and application thereof. Background Art
[0002] In recent years, with the progress of science and technology and society, the new energy industry is showing vigorous vitality. The emergence of lithium-ion batteries (LIB), sodium-ion batteries (SIB) and magnesium-ion batteries (MIB) has promoted the development and application of new energy. At present, lithium-ion batteries dominate the energy storage market, but the uneven distribution of lithium resources and the rapid growth of market demand have led to a sharp increase in the unit price of lithium. Therefore, the market urgently needs to develop secondary battery technology that can replace lithium-ion batteries to get rid of the difficulty of lithium resource shortage. Since lithium and sodium are in the same main group in the periodic table, they have similar chemical properties, so sodium-ion batteries are widely considered to be a substitute for lithium-ion batteries. In addition, compared with lithium-ion batteries, sodium-ion batteries have the following advantages in theory: (1) sodium resources are widely distributed, cheap and low cost; (2) sodium-ion batteries will not have over-discharge characteristics during use and can be discharged to zero volts; (3) sodium-ion batteries have higher safety. These advantages make sodium-ion batteries have broad application prospects in the current market.
[0003] However, sodium-ion batteries have not yet been industrialized like lithium-ion batteries. This is because existing sodium-ion batteries have low electrode discharge capacity, short cycle life, and poor rate performance. These problems make it difficult for the materials to meet the needs of market applications. The negative electrode material is one of the most critical components of sodium-ion batteries, and its performance directly affects the performance of sodium-ion batteries. Currently, commercial lithium-ion batteries mostly use graphite as the negative electrode material, but because the distance between graphite layers is small, it is not suitable for sodium ion embedding and extraction. Therefore, when graphite prepared by conventional methods is used as a sodium storage negative electrode material, the electrochemical performance of sodium-ion batteries cannot meet the requirements. Summary of the invention
[0004] The object of the present invention is to provide a carbon black particle and a preparation method and application thereof. The carbon black particle obtained by the preparation method provided by the present invention has excellent electrochemical properties when used as a negative electrode material for a sodium ion battery.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing carbon black particles, comprising the following steps:
[0007] (1) heating a tubular furnace to a dehydrogenation polymerization reaction temperature under the protection of an inert gas; the dehydrogenation polymerization reaction temperature is 700 to 900° C.;
[0008] (2) introducing acetylene gas into the tubular furnace heated to the dehydrogenation polymerization reaction temperature in step (1) to carry out a dehydrogenation polymerization reaction to obtain carbon black; the rate of introducing the acetylene gas is 100 to 300 mL / min;
[0009] (3) activating the carbon black obtained in step (2) to obtain carbon black particles.
[0010] Preferably, the temperature of the dehydrogenation polymerization reaction in step (1) is 800-900°C.
[0011] Preferably, the heating rate in step (1) is 1 to 10° C. / min.
[0012] Preferably, the rate of introducing acetylene gas in step (2) is 200-300 mL / min.
[0013] Preferably, the insulation time of the dehydrogenation polymerization reaction in step (2) is 20 to 50 minutes.
[0014] Preferably, after the dehydrogenation polymerization reaction in step (2), the temperature is lowered to room temperature under the protection of an inert gas.
[0015] Preferably, the activation method in step (3) is nitric acid activation.
[0016] The present invention also provides carbon black particles prepared by the preparation method described in the above technical solution, wherein the particle size of the carbon black particles is 136 to 287 nm.
[0017] The present invention also provides the use of the carbon black particles described in the above technical solution as a negative electrode material for a sodium ion battery.
[0018] The present invention provides a method for preparing carbon black particles, comprising the following steps: heating a tubular furnace to a dehydrogenation polymerization reaction temperature under the protection of an inert gas; the temperature of the dehydrogenation polymerization reaction is 700-900°C; passing acetylene gas into the tubular furnace heated to the dehydrogenation polymerization reaction temperature to carry out a dehydrogenation polymerization reaction to obtain carbon black; the rate of passing acetylene gas is 100-300mL / min; activating the carbon black to obtain carbon black particles. The present invention can regulate the particle size of carbon black by controlling the temperature of the dehydrogenation polymerization reaction and the rate of passing acetylene, so that the particle size has a suitable particle size and a large specific surface area; the present invention can open the pores in the carbon black by activating the carbon black, which is more conducive to the insertion and extraction of sodium ions when the carbon black particles are used as the negative electrode material of a sodium ion battery. The results of the embodiment show that the sodium ion battery assembled with the carbon black particles prepared by the present invention as the negative electrode material has a first-cycle charge and discharge capacity of 414.66 mAh / g. After 180 cycles, its discharge capacity remains at 112.36 mAh / g, showing excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The SEM images of the carbon black particles prepared in Example 1 of the present invention at different magnifications;
[0020] Figure 2 The SEM images of the carbon black particles prepared in Example 2 of the present invention at different magnifications;
[0021] Figure 3 The SEM images of the carbon black particles prepared in Example 3 of the present invention at different magnifications;
[0022] Figure 4 The SEM images of the carbon black particles prepared in Comparative Example 1 of the present invention at different magnifications;
[0023] Figure 5 The SEM images of carbon black particles prepared in Comparative Example 2 of the present invention at different magnifications;
[0024] Figure 6 The cyclic charge-discharge curve of CB-1 prepared in Example 1 of the present invention;
[0025] Figure 7 The cyclic charge-discharge curve of CB-2 prepared in Example 2 of the present invention;
[0026] Figure 8 The cyclic charge-discharge curve of CB-3 prepared in Example 3 of the present invention;
[0027] Fig. 9 The cycle performance and coulombic efficiency diagrams of CB-1, CB-2 and CB-3 prepared in Examples 1 to 3 of the present invention;
[0028] Fig.10 The rate performance diagrams of CB-1, CB-2 and CB-3 prepared in Examples 1 to 3 of the present invention. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing carbon black particles, comprising the following steps:
[0030] (1) heating a tubular furnace to a dehydrogenation polymerization reaction temperature under the protection of an inert gas; the dehydrogenation polymerization reaction temperature is 700 to 900° C.;
[0031] (2) introducing acetylene gas into the tubular furnace heated to the dehydrogenation polymerization reaction temperature in step (1) to carry out a dehydrogenation polymerization reaction to obtain carbon black; the rate of introducing the acetylene gas is 100 to 300 mL / min;
[0032] (3) activating the carbon black obtained in step (2) to obtain carbon black particles.
[0033] The present invention heats the tubular furnace to a dehydrogenation polymerization reaction temperature under the protection of an inert gas.
[0034] In the present invention, the temperature of the dehydrogenation polymerization reaction is 700-900° C., preferably 800-900° C. The present invention controls the temperature of the dehydrogenation polymerization reaction within the above range, which is more conducive to obtaining carbon black particles with smaller and uniform particle size.
[0035] In the present invention, the inert gas is preferably argon. In the present invention, the temperature is increased under the protection of the inert gas, and the air in the tube furnace can be discharged. In the present invention, the introduction rate of the inert gas is preferably 50 to 250 mL / min, and more preferably 50 to 100 mL / min. The present invention is more conducive to fully discharging the air in the tube furnace at the above-mentioned inert gas introduction rate.
[0036] In the present invention, the heating rate to the dehydrogenation polymerization reaction temperature is preferably 1 to 10° C. / min, more preferably 5 to 10° C. / min.
[0037] In the present invention, after the tubular furnace is heated to the dehydrogenation polymerization reaction temperature under the protection of inert gas, acetylene gas is introduced into the tubular furnace heated to the dehydrogenation polymerization reaction temperature to carry out dehydrogenation polymerization reaction to obtain carbon black.
[0038] In the present invention, the rate of introduction of the acetylene gas is 100 to 300 mL / min, preferably 200 to 300 mL / min. The present invention controls the introduction rate of the acetylene gas to adjust the particles of the carbon black.
[0039] In the present invention, the holding time of the dehydrogenation polymerization reaction is preferably 20 to 50 minutes, more preferably 30 minutes. By controlling the holding time within the above range, the present invention can make acetylene fully react.
[0040] In the present invention, after the dehydrogenation polymerization reaction, the temperature is preferably lowered to room temperature under the protection of an inert gas. In the present invention, the inert gas is preferably argon. The present invention has no particular limitation on the cooling rate of the temperature reduction to room temperature, and the temperature can be naturally lowered to room temperature. The present invention can maintain a high purity of carbon black by lowering the temperature under the protection of an inert gas.
[0041] After obtaining the carbon black, the present invention activates the carbon black to obtain carbon black particles.
[0042] In the present invention, the activation method is preferably nitric acid activation, and the nitric acid activation method preferably comprises: mixing carbon black with a nitric acid solution, heating and stirring, and then filtering, washing and drying to obtain carbon black particles. The present invention can open the pores in the carbon black through activation.
[0043] In the present invention, the concentration of the nitric acid solution is preferably 10-20 mol / L, more preferably 15 mol / L. The use of the nitric acid solution with the above concentration is more conducive to dissolving impurities in the carbon black pores.
[0044] In the present invention, the heating temperature is preferably 20 to 80° C., more preferably 40 to 80° C. The present invention can promote the dissolution of impurities by nitric acid by heating.
[0045] In the present invention, the stirring time is preferably 1 to 5 hours, more preferably 2 to 3 hours. The present invention has no special limitation on the stirring speed, and a conventional speed can be used for adjustment. The present invention promotes mass transfer through stirring, thereby improving the activation effect of nitric acid on carbon black.
[0046] The present invention has no special limitation on the filtering, washing and drying methods, and conventional filtering, washing and drying methods can be used. In the present invention, the washing agent is preferably deionized water; the drying temperature is preferably 40 to 80°C, more preferably 60 to 80°C, and the drying time is preferably 1 to 12 hours, more preferably 2 to 6 hours.
[0047] The method provided by the present invention is simple to operate. By controlling the temperature of the dehydrogenation polymerization reaction and the introduction rate of acetylene, the particle size of the carbon black can be regulated to have a suitable particle size and a large specific surface area. The present invention can open the pores in the carbon black by activating the carbon black, which is more conducive to the insertion and extraction of sodium ions when the carbon black particles are used as the negative electrode material of the sodium ion battery.
[0048] The present invention also provides carbon black particles prepared by the preparation method described in the above technical solution, wherein the particle size of the carbon black particles is 136 to 287 nm.
[0049] The present invention also provides the use of the carbon black particles described in the above technical solution as sodium ion negative electrode materials.
[0050] The present invention has no special limitation on the application method of the carbon black particles as the sodium ion negative electrode material, and conventional application methods can be used.
[0051] The present invention can make the prepared carbon black particles have a suitable particle size and a large specific surface area by controlling the preparation method, which is more conducive to the insertion and extraction of sodium ions when the carbon black particles are used as sodium ion negative electrode materials. Therefore, when it is used as a negative electrode material for a sodium ion battery, it has excellent electrochemical performance.
[0052] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] Example 1
[0054] A method for preparing carbon black particles, comprising the following steps:
[0055] (1) introducing argon gas into a tubular furnace at a rate of 50 mL / min, and heating the tubular furnace at a heating rate of 10° C. / min to a dehydrogenation polymerization reaction temperature of 700° C. under argon protection;
[0056] (2) introducing acetylene gas at 200 mL / min into the tubular furnace heated to the dehydrogenation polymerization reaction temperature in step (1), keeping the temperature for 30 min to carry out dehydrogenation polymerization reaction, then turning off the acetylene gas source, cooling to room temperature at a cooling rate of 50° C. / min under argon protection, to obtain carbon black;
[0057] (3) The carbon black obtained in step (2) is placed in 50 mL of 15 mol / L nitric acid solution, and heat treated at 80° C. for 2 h under magnetic stirring at 400 r / min. After filtering, it is fully washed with deionized water until neutral, and then filtered, placed in a vacuum drying oven, and dried at a vacuum environment temperature of 80° C. for 24 h to obtain carbon black particles, which are recorded as CB-1.
[0058] Example 2
[0059] A method for preparing carbon black particles, comprising the following steps:
[0060] (1) introducing argon gas into a tubular furnace at a rate of 50 mL / min, and heating the tubular furnace at a heating rate of 10° C. / min to a dehydrogenation polymerization reaction temperature of 900° C. under argon protection;
[0061] (2) introducing acetylene gas at 200 mL / min into the tubular furnace heated to the dehydrogenation polymerization reaction temperature in step (1), keeping the temperature for 30 min to carry out dehydrogenation polymerization reaction, then turning off the acetylene gas source, cooling to room temperature at a cooling rate of 50° C. / min under argon protection, to obtain carbon black;
[0062] (3) The carbon black obtained in step (2) is placed in 50 mL of 15 mol / L nitric acid solution, and heat treated at 80° C. for 2 h under magnetic stirring at 400 r / min. After filtering, it is thoroughly washed with deionized water until neutral, and then filtered, placed in a vacuum drying oven, and dried at a vacuum environment temperature of 80° C. for 24 h to obtain carbon black particles, which are recorded as CB-2.
[0063] Example 3
[0064] A method for preparing carbon black particles, comprising the following steps:
[0065] (1) introducing argon gas into a tubular furnace at a rate of 50 mL / min, and heating the tubular furnace at a heating rate of 10° C. / min to a dehydrogenation polymerization reaction temperature of 900° C. under argon protection;
[0066] (2) introducing acetylene gas at 300 mL / min into the tubular furnace heated to the dehydrogenation polymerization reaction temperature in step (1), keeping the temperature for 30 min to carry out dehydrogenation polymerization reaction, then turning off the acetylene gas source, cooling to room temperature at a cooling rate of 50° C. / min under argon protection, to obtain carbon black;
[0067] (3) The carbon black obtained in step (2) is placed in 50 mL of 15 mol / L nitric acid solution, and heat treated at 80° C. for 2 h under magnetic stirring at 400 r / min. After filtering, it is fully washed with deionized water until neutral, and then filtered, placed in a vacuum drying oven, and dried at a vacuum environment temperature of 80° C. for 24 h to obtain carbon black particles, which are recorded as CB-3.
[0068] Comparative Example 1
[0069] A method for preparing carbon black particles, comprising the following steps:
[0070] (1) introducing argon gas into a tubular furnace at a rate of 200 mL / min, and heating the tubular furnace at a heating rate of 10° C. / min to a dehydrogenation polymerization reaction temperature of 900° C. under argon protection;
[0071] (2) introducing acetylene gas at a rate of 100 mL / min and argon gas at a rate of 200 mL / min into the tubular furnace heated to the dehydrogenation polymerization reaction temperature in step (1), keeping the temperature for 30 minutes to carry out dehydrogenation polymerization reaction, then turning off the acetylene gas source, cooling to room temperature at a cooling rate of 50° C. / min under the protection of argon gas, and obtaining carbon black;
[0072] (3) The carbon black obtained in step (2) is placed in 50 mL of 15 mol / L nitric acid solution, and heat treated at 80° C. for 2 h under magnetic stirring at 400 r / min. After filtering, it is fully washed with deionized water until neutral, and then filtered, placed in a vacuum drying oven, and dried at a vacuum environment temperature of 80° C. for 24 h to obtain carbon black particles, which are recorded as CB-4.
[0073] Comparative Example 2
[0074] A method for preparing carbon black particles, comprising the following steps:
[0075] (1) introducing argon gas into a tubular furnace at a rate of 250 mL / min, and heating the tubular furnace at a heating rate of 10° C. / min to a dehydrogenation polymerization reaction temperature of 900° C. under argon protection;
[0076] (2) acetylene gas at a rate of 125 mL / min and argon gas at a rate of 250 mL / min are simultaneously passed through the tubular furnace of step (1) to raise the temperature to the dehydrogenation polymerization reaction temperature, and the temperature is kept for 30 minutes to carry out dehydrogenation polymerization reaction, and then the acetylene gas source is turned off, and the mixture is cooled to room temperature at a cooling rate of 50° C. / min under the protection of argon gas to obtain carbon black;
[0077] (3) The carbon black obtained in step (2) is placed in 50 mL of 15 mol / L nitric acid solution, and heat treated at 80° C. for 2 h under magnetic stirring at 400 r / min. After filtering, it is fully washed with deionized water until neutral, and then filtered, placed in a vacuum drying oven, and dried at a vacuum environment temperature of 80° C. for 24 h to obtain carbon black particles, which are recorded as CB-5.
[0078] Test Case
[0079] (1) The carbon black particles prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested using a scanning electron microscope. The SEM images of the carbon black particles prepared in Example 1 at different magnifications are as follows: Figure 1 As shown; SEM images of the carbon black particles prepared in Example 2 at different magnifications are shown Figure 2 As shown; SEM images of carbon black particles prepared in Example 3 at different magnifications are shown Figure 3 As shown; SEM images of carbon black particles prepared in Comparative Example 1 at different magnifications are shown Figure 4 As shown; SEM images of carbon black particles prepared in Comparative Example 2 at different magnifications are shown Figure 5 The particle size ranges of the carbon black particles prepared in Examples 1 to 3 and Comparative Examples 1 to 5 are shown in Table 1.
[0080] Table 1 Particle size range of carbon black particles prepared in Examples 1 to 3 and Comparative Examples 1 to 5
[0081] sample Temperature ℃ Gas flow mL / min Particle size range nm Average particle size nm CB-1 700 <![CDATA[C2H2200]]> 240.7~47.4 286.9 CB-2 900 <![CDATA[C2H2200]]> 206.3~79.7 242.9 CB-3 900 <![CDATA[C2H2300]]> 118.6~155.0 136.7 CB-4 900 <![CDATA[C2H2100Ar200]]> 815.5~1057.1 961.7 CB-5 900 <![CDATA[C2H2125Ar250]]> 616.1~974.4 769.7
[0082] from Figures 1 to 5As can be seen from Table 1, due to the relatively low temperature, CB-1 caused particle agglomeration during the cracking process, resulting in large particles as shown in the figure. Due to the higher temperature and larger gas flow rate, CB-3 accelerated the acetylene cracking rate, resulting in the smallest prepared particle size, with a particle size range of 118.6-155.0nm and an average particle size of 136.7nm. Due to the introduction of mixed gas, the acetylene atmosphere of CB-4 and CB-5 was diluted, so the speed was slow under high-temperature cracking, and a large amount of acetylene did not have time to crack, resulting in larger sample particles, with average particle sizes of 961.7nm and 769.7nm respectively. It can be seen that the higher the temperature and the greater the gas flow rate of acetylene, the smaller the particle size of the produced carbon black particles.
[0083] (2) Analysis of cycle performance test results
[0084] The method of cycle performance test is:
[0085] a. Preparation of negative electrode
[0086] The negative electrode of the sodium ion battery of the present invention is prepared by a conventional slurry coating method. The electrode sheet is composed of an active material (carbon black particles prepared in the embodiment of the present invention), a conductive agent SuperP, a water-based adhesive CMC and a current collector copper foil.
[0087] First, 0.32g of active substance, 0.04g of SuperP, and 0.04g of CMC (mass ratio 8:1:1) were weighed on an analytical balance. CMC was placed in an agate mortar, and then SuperP was added and ground for 30 minutes until no particles were visible to the naked eye. Then, the active substance was added and mixed with the former, and deionized water was added and ground for 2 hours until a uniform slurry with moderate viscosity and no obvious particles was formed.
[0088] Cut the copper foil into a 9cm×18cm rectangle, and clean both sides of the copper foil three times with anhydrous ethanol. Then put the copper foil on the coating machine, evenly apply the ground slurry on the copper foil, and use a scraper with a thickness of 100μm to apply it. After the coating is completed, cover the coating machine, and then heat it from room temperature to 80℃ and dry it for 2min. After drying, put it in a blast drying oven and dry it for 24h.
[0089] After the copper foil is dried, it is cut into electrode sheets with a diameter of 12 mm using a cutting machine, and the mass of the electrode sheets is weighed and recorded.
[0090] b. Assembly of button cell batteries
[0091] Prepare the raw materials required for the sodium-ion battery assembly (including positive and negative electrode shells, active materials, spring sheets, and gaskets) and put them into a glove box filled with argon gas with water and oxygen content less than 0.1ppm. Use 1M NaPF6 dissolved in a mixed solvent (EC / DMC / EMC, v:v:v=1:1:1) as an electrolyte, a sodium sheet as a counter electrode, and a glass fiber membrane as a diaphragm.
[0092] The assembly process of the CR2032 button battery is as follows:
[0093] First put the positive electrode shell in place;
[0094] Then use tweezers to place the electrode sheet in the center of the positive electrode shell.
[0095] Select a smooth and wrinkle-free membrane and place it on the active substance
[0096] Add 35 μL of electrolyte evenly around the diaphragm.
[0097] Then tear off the film on the surface of the sodium sheet and put the sodium sheet in the middle
[0098] Align the gasket and spring sheet on the sodium sheet.
[0099] Then cover the negative electrode shell
[0100] Finally, the battery is sealed using a small hydraulic button battery packaging machine.
[0101] c. Charge and discharge performance test of button battery
[0102] After the button cell assembly was completed, it was left to stand for 24 hours. At room temperature, the constant current charge-discharge cycle performance test was performed using the NEWARE BTS 7.6.X test system at a fixed voltage of 0.01V and 3.0V and 25°C. The cycle was tested at a current density of 200mA / g. The rate was tested at current densities of 50, 100, 200, 500, 1000 and 2000mA / g. The cycle charge-discharge curve of CB-1 prepared in Example 1 is shown in the figure below. Figure 6 As shown; the cyclic charge-discharge curve of CB-2 prepared in Example 2 is as shown Figure 7 The cyclic charge-discharge curve of CB-3 prepared in Example 3 is shown in Figure 8 The cycle performance and coulombic efficiency of CB-1, CB-2 and CB-3 prepared in Examples 1 to 3 are shown in the figure. Fig. 9 As shown; the rate performance diagrams of CB-1, CB-2 and CB-3 prepared in Examples 1 to 3 are as shown Fig.10 shown.
[0103] from Figures 6 to 9It can be concluded that the first-round discharge capacity of CB-1 is 205.64mAh / g. After 180 cycles, its discharge capacity remains at 81.62mAh / g. When the low current density is restored in the rate test, it can still be restored to a higher capacity. The first-round charge and discharge capacity of sample CB-2 is 197.21mAh / g. After 180 cycles, its discharge capacity remains at 90.43mAh / g. When the low current density is restored in the rate test, it can still be restored to a higher capacity. The first-round charge and discharge capacity of sample CB-3 is 414.66mAh / g. After 180 cycles, its discharge capacity remains at 112.36mAh / g. When the low current density is restored in the rate test, it can still be restored to a higher capacity.
[0104] It can be seen from the above results that the present invention controls the particle size of the carbon black particles by controlling the temperature of the dehydrogenation polymerization reaction and the introduction rate of acetylene gas. At a higher reaction temperature and a faster introduction rate, it is more conducive to obtaining smaller carbon black particles with a narrow particle size distribution, and it has better electrochemical performance when used as a negative electrode material for sodium ion batteries.
[0105] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing carbon black particles, The following steps are involved: (1) heating a tubular furnace to a dehydrogenation polymerization reaction temperature under the protection of an inert gas; the dehydrogenation polymerization reaction temperature is 700 to 900° C.; (2) introducing acetylene gas into the tubular furnace heated to the dehydrogenation polymerization reaction temperature in step (1) to carry out a dehydrogenation polymerization reaction to obtain carbon black; the rate of introducing the acetylene gas is 100 to 300 mL / min; (3) activating the carbon black obtained in step (2) to obtain carbon black particles.
2. The preparation method according to claim 1, It is characterized in that The temperature of the dehydrogenation polymerization reaction in step (1) is 800-900°C.
3. The preparation method according to claim 1, It is characterized in that The heating rate in step (1) is 1 to 10°C / min.
4. The preparation method according to claim 1, It is characterized in that The rate of introducing acetylene gas in step (2) is 200-300 mL / min.
5. The preparation method according to claim 1, It is characterized in that The insulation time of the dehydrogenation polymerization reaction in step (2) is 20 to 50 minutes.
6. The preparation method according to claim 1, It is characterized in that After the dehydrogenation polymerization reaction in step (2), the temperature is lowered to room temperature under the protection of an inert gas.
7. The preparation method according to claim 1, It is characterized in that The activation method in step (3) is nitric acid activation.
8. The carbon black particles prepared by the preparation method according to any one of claims 1 to 7, wherein the particle size of the carbon black particles is 136 to 287 nm.
9. Use of the carbon black particles according to claim 8 as negative electrode materials for sodium ion batteries.
Citation Information
Patent Citations
Granular acetylene black, process for production thereof, and composition
CN101528864A
Druss, preparation method and preparation equipment thereof
CN106543777A
Conductive additive for supercapacitor as well as preparation method and application thereof
CN111925672A
Conductive carbon black for inhibiting tailing factor, preparation method and equipment thereof, electrode slurry and secondary battery
CN118388980A
